Food insecurity characteristics and related factors among pregnant women attending antenatal care in Karachi - Nasreen Fatima; Muhammad Saad Khan; Marium Fatima; Maliha Khalid; Izere Salomon; Muhammad Tarish Abro (BMC Pregnancy and Childbirth)
Abstract Background Food insecurity (FI), defined as the lack of consistent access to sufficient and nutritious food, remains a critical public health issue in low- and middle-income countries. In Pakistan, approximately 37% of the population experiences FI. Pregnant women are particularly vulnerable, as nutritional challenges during pregnancy may affect their health-seeking behaviors. This study aimed to describe the prevalence of household food insecurity and patterns of antenatal care (ANC) utilization among pregnant women in Karachi, Pakistan. Methods This descriptive cross-sectional study was conducted at the Department of Gynecology and Obstetrics, Jinnah Postgraduate Medical Center, Karachi, from June to August 2024. Through convenience sampling, 358 pregnant women in their third month of gestation or later were enrolled in the study. Data were collected using a structured questionnaire that included the validated household food security access scale (HFIAS). Data were analyzed using SPSS version 25. Frequencies, percentages, and cross-tabulations were used for description. Results The mean age of the 358 participants was 26.45 ± 4.9 years. A total of 60.3% of the respondents were from food-insecure households. ANC utilization was reported by 89.3% of the participants. The highest ANC attendance was observed among women aged 21–26 years, women with primary or secondary education, and housewives. Most ANC users have household incomes ranging between PKR 30,000 and 60,000. ANC use was common among multigravida women and among those without any prior stillbirths or abortions. Most women who underwent ANC were informed or guided about their importance. Conclusion A considerable proportion of pregnant women in Karachi reported utilizing ANC services, including those from food-insecure households. Various demographic, educational, and reproductive characteristics of ANC attendance have been described. These findings provide an overview of ANC utilization patterns in an urban tertiary care setting and highlight the coexistence of food insecurity among ANC users.